Pengaruh Implementasi Program Keluarga Harapan Terhadap Kesejahteraan Masyarakat di Kelurahan Baktijaya Kota Depok - Arum, Dewi Sekar; Sugiyanto, M.Si, Eko (Universitas Nasional, 2023)
In an effort to improve community welfare, the government has, among other things, launched the Family Hope Program (PKH) as a program to provide conditional social assistance to poor families (KM) who are designated as PKH beneficiary families. Even though this program has proven to be quite successful in overcoming poverty, its implementation still requires further program efforts in the form of vocational training, micro-entrepreneurship, and collaboration with various private institutions. This is a demand for local governments so that the implementation of the PKH program can have a positive influence on community welfare. Baktijaya Village, Depok City is one of the villages that is part of the Ministry of Social Affairs' program. In the midst of an increasing trend in the average poverty rate every year in Depok City, it is not easy to implement policies because implementation is not just about carrying out what has been outlined. According to Grindel, there are a number of measures of success that serve as a reference and must be taken into account, namely those related to the content of policy and the implementation environment (context of implementation). This research aims to determine the effect of implementing the PKH policy on community welfare in Baktijaya Village, Depok City. This research uses quantitative methods. The results of the research show that there is a quite positive and significant influence of the implementation of the PKH policy on the welfare of the community in Baktijaya Village, Depok City. Dalam upaya meningkatkan kesejahteraan masyarakat, pemerintah antara lain telah meluncurkan Program Keluarga Harapan (PKH) sebagai program pemberian bantuan sosial bersyarat kepada Keluarga Miskin (KM) yang ditetapkan sebagai keluarga penerima manfaat PKH. Meskipun program tersebut terbukti cukup berhasil dalam menanggulangi kemiskinan, akan tetapi dalam implementasinya masih memerlukan upaya program lanjutan dalam bentuk pelatihan vokasional, micro-entrepreneurship, dan kerja sama dengan berbagai lembaga swasta. Ini menjadi tuntutan bagi pemerintah daerah agar implementasi program PKH bisa memberikan pengaruh positif terhadap kesejahteraan masyarakat. Kelurahan Baktijaya Kota Depok merupakan salah satu kelurahan yang menjadi program Kementerian Sosial. Di tengah kecenderungan semakin meningkatnya rata-rata angka kemiskinan tiap tahun di Kota Depok, tidaklah mudah mengimplementasikan kebijakan karena implementasi itu bukan sekadar melaksanakan apa yang telah digariskan. Menurut Grindel, ada sejumlah ukuran keberhasilan yang menjadi acuan dan harus diperhatikan, yaitu terkait isi kebijakan (content of policy) dan lingkungan implementasi (context of implementation). Penelitian ini bertujuan untuk mengetahui pengaruh implementasi kebijakan PKH terhadap kesejahteraan masyarakat di Kelurahan Baktijaya Kota Depok. Penelitian ini menggunakan metode kuantitatif. Hasil penelitian menunjukkan bahwa terdapat pengaruh yang cukup positif dan signifikan implementasi kebijakan PKH terhadap kesejahteraan masyarakat di Kelurahan Baktijaya, Kota Depok.